Demoralizacja i czyny karalne według Ustawy o wspieraniu i resocjalizacji nieletnich – wybrane zagadnienia - Wojnicz, Piotr; Mościcka , Diana (Civitas et Lex, 2023)
The article describes selected issues concerning demoralization and punishable crimes referred to in the Act of 9 June 2022 on juvenile support and resocialization. In this new legal act, which came into force in September 2022, many significant issues have been stated, among others the minimum age of over 10 years old and the condition in the form of a stipulation „and are not of age” for individuals to whom provisions of law with regard to preventing demoralization are applied. The series of circumstances proclaiming juvenile demoralization has been amended and the list of offences defined as a punishable crime has been extended. Additionally, new regulations have been introduced to enable school principals and the police to take (under certain conditions) educational measures against juvenile offenders. The Act also contains modified definition of a punishable act. What has been added to the previously specified educational measures (to which, in turn, putting a minor in a regional juvenile education centre has been added) and the correctional measure is the medical measure. The subject of the article is an analysis of the current legal provisions regulating the matters of minors. The multidimensional nature of the issue determined the choice of research methods. The following methods were used: formal-dogmatic, historical-legal or comparative. At the same time, it should be emphasized that the material contains an analysis of the applicable legal act.